INFLUENCE DISEASE SPOTS LEAVES ON COFFEE PLANTS AND THEIR CONTROL - Deni Alamsyah; Luki Sugiardi Pasaribu; Muhammad Jody Alfiansyah (ITScience (Information Technology and Science), 2022)
The disease spotting leaf is one disease in coffee plants caused by mold Cercospora caffeicola, also known as brown eyespot. Disease spotting leaf could attack part leaf coffee plant and the fruit (Harni et al., 2015) . The disease this can attack coffee plants during the seedling period until with plant ripens. If already severe, attack disease even could spread to coffee fruit. Symptom attack disease spotting leaf be marked with appearance spots colored yellow then changed Becomes spotting brown on leaves. The basic method in this writing is descriptive. The data used are the results of previous studies relating to the disease spotting leaf on coffee plants and their control. The result of this research is that fertilization balance is highly recommended for maintaining healthy plants to endure to attack disease. Besides that, spraying fungicide live (using Actinomycetes bacteria) and chemicals also help for push growth mold reason spotting leaves.